Frequency of Bacterial Vaginosis Amongst Pregnant Women Attending the Tertiary Care Hospital - Zakia Khan, Hina Khan, Maimoona Azam, Shaheer Khan, Haris Khan, Saira Bano (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The poly-microbial illness known as bacterial vaginosis is defined by the depletion of the normal vaginal flora. Bacterial vaginosis is a common problem in pregnant women. Objective: To find out the frequency of bacterial vaginosis amongst pregnant women attending the tertiary care Methodology: This study was descriptive cross sectional carried out at the Gynecology department of Khalifa Gulnawaz Hospital, Bannu for duration of six months from January 2022 to July 2022. Under aseptic condition, vaginal swab was taken by using high vaginal swab procedure and sent to the concerned laboratory for determination of bacterial vaginosis. All the analysis of data was done by using IBM SPSS version 24. Results: In the current study, totally 250 pregnant women were included. The mean age was 28.12 years with standard deviation of 9.15. The mean (SD) gestational age was 24.15 (3.25) weeks. Out of 250 pregnant women, bacterial vaginosis was observed in 48 (19%) patients. Conclusion: Our study concludes that bacterial vaginosis is highly prevalent in pregnant women. Awareness programs should be started on national level to educate women about bacterial vaginosis during pregnancy. Keywords: Prevalence; Bacterial vaginosis; Pregnancy